The principles studied in islamic political thought: revisiting modern political discourse - Aziz, M. Abdul (IJISH (International Journal of Islamic Studies and Humanities), 2023)
Islam as the way of life covers all aspects of human life. As political science; mainly the study of politics, state, and government, is part of life, Islam encompasses all these issues of this discipline. Islam rightly mentioned modern thought humanitarianism, universalism, equity, and justice in quranic verse and prophetic ideals more than a thousand years ago. Tawhid, Adalah, Hurriyah, Shura, and Khilafah the core tenets of Islamic Political thought are enshrined into the contemporary discourse of political science. The study is an attempt to quest for the principles of political science as prescribed in the Holy Qur’an (the revelation from Almighty Allah) and the Hadith (the words, actions, and approvals of Prophet Muhammad), the practices and governance system of four rightly guided Caliphs. All these sources state that man is the representative (Caliph) of Allah and his responsibility is to convey the messages of Allah and undertake these into practice. The study explores that in Islam, there is the existence of political principles and practices as studied in contemporary political science. Besides, human beings as a representative of Allah should practice the Islamic political principles to exercise power in a state following Al-Qur’anic guidance and the ideals and practices of Prophet Muhammad (sm.) and the Caliphs of Khulafa-e-Rashidun as well.